2002
DOI: 10.1128/cmr.15.3.506-526.2002
|View full text |Cite
|
Sign up to set email alerts
|

Legionella and Legionnaires' Disease: 25 Years of Investigation

Abstract: There is still a low level of clinical awareness regarding Legionnaires' disease 25 years after it was first detected. The causative agents, legionellae, are freshwater bacteria with a fascinating ecology. These bacteria are intracellular pathogens of freshwater protozoa and utilize a similar mechanism to infect human phagocytic cells. There have been major advances in delineating the pathogenesis of legionellae through the identification of genes which allow the organism to bypass the endocytic pathways of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
1,382
3
69

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,457 publications
(1,503 citation statements)
references
References 266 publications
17
1,382
3
69
Order By: Relevance
“…The primary method of LD diagnosis is UAT since this modality identifies 81% to 97% of LD infections compared to only 5% to 9% by culture [15,28]. The UAT is simple and it can rapidly and accurately (sensitivity, 60% to 80%; specificity, >99%) identify L. pneumophila serogroup 1 [17,28]. However, culture remains important because 14% to 20% of LD infections are caused by non-serogroup 1 Legionella species [15,17] that UAT cannot detect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary method of LD diagnosis is UAT since this modality identifies 81% to 97% of LD infections compared to only 5% to 9% by culture [15,28]. The UAT is simple and it can rapidly and accurately (sensitivity, 60% to 80%; specificity, >99%) identify L. pneumophila serogroup 1 [17,28]. However, culture remains important because 14% to 20% of LD infections are caused by non-serogroup 1 Legionella species [15,17] that UAT cannot detect.…”
Section: Discussionmentioning
confidence: 99%
“…The UAT is simple and it can rapidly and accurately (sensitivity, 60% to 80%; specificity, >99%) identify L. pneumophila serogroup 1 [17,28]. However, culture remains important because 14% to 20% of LD infections are caused by non-serogroup 1 Legionella species [15,17] that UAT cannot detect. Notably, L. pneumophila from the present patient survived in a non-selective medium for one week and another study has shown that L. pneumophila could survive in standard blood culture broth medium [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several species, in particular Legionella pneumophila and Legionella longbeachae, are pathogenic to humans (1)(2)(3). Because of the development of artificial water systems, such as air conditioning, Legionnaires' disease has emerged as a significant health threat in modern societies (4). Inhalation of L. pneumophila in contaminated aerosols allows the pathogen to reach the alveoli of the lung, where they can be phagocytosed by host macrophages.…”
mentioning
confidence: 99%
“…5 Legionnaires' disease is caused by numerous species of Legionella, bacteria that are ubiquitous in natural and man-made aquatic environments. 6 Acquisition of legionnaires' disease usually occurs following the aspiration or inhalation of aerosols from contaminated potable water or cooling towers. [7][8][9][10][11][12][13][14] Most hospital-acquired outbreaks of legionnaires' disease have been associated with the contamination of hospital drinking water with Legionella species.…”
mentioning
confidence: 99%